Transcranial magnetic stimulation of right dorsolateral prefrontal cortex does not affect associative retrieval in healthy young or older adults - Paul F. Hill; Erin D. Horne; Joshua D. Koen; Michael D. Rugg (NeuroImage: Reports)
We examined whether post-retrieval monitoring processes supporting memory performance are more resource limited in older adults than younger individuals. We predicted that older adults would be more susceptible to an experimental manipulation that reduced the neurocognitive resources available to support post-retrieval monitoring. Young and older adults received transcranial magnetic stimulation (TMS) to the right dorsolateral prefrontal cortex (DLPFC) or a vertex control site during an associative recognition task. The right DLPFC was selected as a TMS target because the region is held to be a key member of a network of regions engaged during retrieval monitoring and is readily accessible to administration of TMS. We predicted that TMS to the right DLPFC would lead to reduced associative recognition accuracy, and that this effect would be more prominent in older adults. The results did not support this prediction. Recognition accuracy was significantly reduced in older adults relative to their younger counterparts, but the magnitude of this age difference was unaffected following TMS to the right DLPFC or vertex. These findings suggest that TMS to the right DLPFC was insufficient to deplete the neurocognitive resources necessary to support post-retrieval monitoring.